Bridge Load Rating Through Proof Load Testing for Shear at Dapped Ends of Prestressed Concrete Girders - Zhou, Y. Edward; Guzda, Mark R. (Frontiers in Built Environment, 2020)
Load ratings of the 1967 built I-195 westbound bridge over Seekonk River in Rhode Island are governed by shear at the dapped ends of prestressed concrete (PSC) girders. Insufficient analytical load ratings, in combination with visible shear cracks at the dapped ends, prompted the need for a refined method of load rating through load testing. The proof load testing method was chosen over diagnostic testing for a higher level of reliability due to uncertainties involved in calculating shear capacities of the dapped ends. A proof load test was successfully completed with a maximum proof load of two test trucks of approximately 100,000 lbs each crossing the bridge side-by-side without any signs of distress or nonlinear behavior observed. Vehicle loading dynamic impact was also assessed during the load test. Test measurements indicated full composite action between the bridge deck and the PSC drop-in girders, which was not accounted for in the analytical rating of the dapped ends. Test results suggested that the strut-and-tie and shear-friction analysis methods underestimate the shear resistance of the dapped ends by considering only the stirrup reinforcement and draped prestressing strands within the PSC girder. This paper provides detailed information on bridge proof load testing in general concept and procedure, comparisons with the diagnostic load testing method, field operation, examination of test measurements for linear elastic structural behavior, and determining bridge load ratings based on test results per The Manual for Bridge Evaluation of AASHTO.